The Impact of Brand Love on Consumer Repurchase Intention Mediated by Brand Equity in the Case of Starbucks Indonesia - Teddy Bryan; Darell Setiawan Sutrisno (iBuss Management, 2021)
As the number of coffee shops increase in Indonesia, competitions are increasing and many people believe that in order to strive and thrive in this highly competitive industries, developing love-like brand-consumer relationship (brand love) that results in the stimulation of consumer repurchase intention plays a key role. Talking about brand love, Starbucks is one of the most loved coffee shop brands in Indonesia, despite its more expensive average pricing compared to other majority of coffee shop brands in Indonesia. Therefore, the researchers are determined to understand the elements of brand love in Starbucks Indonesia case to engage consumer repurchase intention. This research will use the brand love theory from Batra et al. (2012); the relationship brand love towards consumer repurchase intention with brand equity as the mediator in the case of Starbucks Indonesia. This research focuses on the Starbucks consumers in Indonesia and will be done by a quantitative approach. Simple random sampling will be used as the sampling design with online questionnaires as the method to obtain the data. In addition, 80 respondents have answered the questionnaire and analysed further with path analysis using multiple linear regression and Sobel Test. As the result, it was found that brand love is partially mediated by brand equity in influencing repurchase intention.Keywords:Brand Love, Brand Equity, Consumer Repurchase Intention.